Line Tracer Robot Navigation System Using Arduino Uno Microntroller With PID Control : Sistem Navigasi Robot Line Tracer Menggunakan Arduino Uno Mikrokontroler Dengan Kontrol PID - Agus Hayatal F; Syamsudduha Syahrorini; A Ahfas; Zidan Nur F; Ali Zaenal A (Academia Open, 2023)
This Study aims to develop a line tracer using Arduino Uno the PID control method. Line tracer robot is a type of robot is a type of robot capable of following a specified path. The PID (Proportional-Integral-Derivative) control used to keep the robot on track by correcting the difference between the actual and the desired position. In this study, 6 photo diode sensors were used, the motor driver used the L293D, and the microcontroller used Arduino Uno. Testing the response of the photo diode sensor had the smallest voltage value at 1,219 Vdc and the largest voltage at 4,875 the result of the motor driver measurements all succeeded in stopping, ccw or cw. The end of testing the line tracer robot using PID control is able to navigate properly without getting of the track. Highlights: Precise Path Following: PID control ensures accurate tracking by correcting position deviations. Sensor Response Evaluation: Photo diode sensor testing reveals voltage range (1.219 Vdc to 4.875 V) for effective line detection. Motor Driver Proficiency: L293D motor driver successfully controls motor functions (stop, ccw, cw) for optimal movement. Keywords : Robot, Line Tracer, PID, Arduino Uno